Determinants of Rehabilitation Follow-Up Non-Adherence Among Stroke Patients in Sibu, Sarawak - Rahim, Nurul Raihana; Jee, Rou Chen (Malaysian Journal of Medical Sciences, 2026)
Background: Sarawak’s vast geography, with remote communities and limited transport infrastructure, poses significant challenges for stroke rehabilitation, yet data on patient attrition in rural Borneo remain limited. This study aimed to evaluate the characteristics of stroke survivors referred for rehabilitation at Hospital Sibu and to identify independent predictors of non-adherence at follow-up. Methods: Inpatient referrals to the Rehabilitation Medicine Department at Hospital Sibu between February 2022 and December 2024 were retrospectively analysed. To avoid competing risk bias, patients who died before their first follow-up were excluded. Factors associated with non-adherence, including functional status, socioeconomic background and travel time, were examined using multivariable binary logistic regression. Results: The analytic cohort comprised 631 survivors (mean age 56.7 ± 15.1 years). Overall, 50.4% (n = 318) defaulted on their first outpatient appointment. Multivariable analysis identified travel time as the dominant barrier: patients living > 30 min from the hospital had a 40-fold higher risk of default (adjusted odds ratio [aOR] = 39.81; 95% confidence interval [CI]: 22.46, 70.58; P < 0.001). Functional dependency also predicted attrition (aOR = 0.98 per Modified Barthel Index point; P < 0.001). Ethnic disparities emerged after adjusting for geography: Chinese ethnicity was associated with lower default risk (aOR = 0.63; P = 0.028), while Melanau ethnicity remained strongly protective (aOR = 0.35; P = 0.001). Conclusion: Post-stroke rehabilitation attrition in central Sarawak is high (50%). Although functional dependency and ethnicity were significant predictors, geographical inaccessibility is the primary driver of non-adherence. Decentralising care is critical to overcoming this logistical barrier.